Making Indonesia Sustainable: Shaping the Law to Reduce Digital Carbon Footprint - Puteri, Dina Silvia (Indonesian Journal of Advocacy and Legal Services, 2024)
In alignment with the commitments made under the Paris Agreement, Indonesia has pledged to significantly reduce its carbon emissions by 2030 as parts of its Enhanced National Determined Contribution (ENDC) within the Indonesia Emas 2045 (Golden Indonesia 2045) Program. However, while the focus has predominantly been on addressing physical carbon footprint, it’s imperative to also consider the burgeoning digital carbon footprint. As Southeast Asia, including Indonesia, faces heightened risks from climate change, exacerbated by the rapid expansion of the digital economic, the need to curb digital carbon emissions becomes increasingly urgent. This paper examines the regulatory landscape concerning digital carbon footprint in Indonesia and explores strategies to mitigate its impact. Through a combination of normative and comparative approaches, the research analyzed existing regulations and draws insights from international best practices. Key research questions include the current regulatory framework governing digital carbon footprint in Indonesia and potential measures to reduce it. The findings aim to inform policymakers and industry stakeholders on effective strategies for reducing digital carbon emissions. Ultimately, the output of this research will contribute to the development of regulations incentivizing businesses to adopt sustainable practices and produce Environmental, Social, and Governance (ESG) reports, thereby advancing Indonesia’s journey toward a greener and more sustainable future.